COST ALLOCATION AND DISTRIBUTION–MERCHANDISE ACCOUNTING. - Burke, Walter L. (The Accounting Review, 1963)
Abstract The article presents an analysis of various methods of allocating and distributing expenses in retail enterprises. Allocation and distribution methods are available which can yield, on a departmental basis, a contribution margin and a reasonably accurate controllable profit figures, but departmental net profit can be obtained only if certain indirect expenses continue to be allocated arbitrarily on some such basis as sales. For product lines and individual items, contribution statements can be prepared by allocating certain expenses on an estimated or computed basis and arbitrarily allocating others. Allocation of costs to products and items, where applicable, is more reliable for establishing prices. For cost analysis, cost control and other managerial purposes than the use of departmental averages and departmental figures. The underlying principles of classification are not ephemeral and methods which are being applied in allocating and distributing costs to products and items may be regarded as applications of fundamental classification principles.